Reliability and validity of the Turkish version of the mental health professionals stigma scale for occupational stress and burnout - Ercan, Feride (The journal of forensic psychiatry & psychology, 2025)
The research was conducted to adapt the Mental Health Professionals Stigma Scale for Occupational Stress and Burnout to Turkish culture and make its validity and reliability. This methodological research was conducted in six different tertiary care hospitals and one state hospital. The research sample consisted of n = 188 mental health professionals (psychiatrists, nurses, psychiatric nurses, psychologists, social workers/experts, occupational therapists), and test-re-test analysis was carried out among 30 professionals. Exploratory factor analysis indicated a three-factor structure with 12 items, accounting for 51.65% of the variation. RMSEA, SRMR, GFI, and χ2/df, which explain the fit indices of the 12-item and 3-factor structure of the scale, were all at an acceptable range. Regarding reliability analysis, the scale was determined to be reliable based on the α coefficient. The research identified that the Turkish version of the scale is a valid and reliable tool for the evaluation of stigmatizing attitudes and beliefs regarding occupational stress and burnout among mental health professionals. It is thought that it will contribute to developing help-seeking and mental health interventions among mental health professionals.